2009
DOI: 10.1152/ajpregu.90753.2008
|View full text |Cite
|
Sign up to set email alerts
|

Normotensive sodium loading in conscious dogs: regulation of renin secretion during β-receptor blockade

Abstract: Renin secretion is regulated in part by renal nerves operating through beta1-receptors of the renal juxtaglomerular cells. Slow sodium loading may decrease plasma renin concentration (PRC) and cause natriuresis at constant mean arterial blood pressure (MAP) and glomerular filtration rate (GFR). We hypothesized that in this setting, renin secretion and renin-dependent sodium excretion are controlled by via the renal nerves and therefore are eliminated or reduced by blocking the action of norepinephrine on the j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…Because ANP plasma levels are elevated under significant salt load and ANP can suppress renin release, a functional role of ANP in the salt-dependent regulation of PRA appears plausible. However, modest, acute salt loading by NaCl infusion at rates that did not elevate plasma ANP levels suppressed the plasma renin activity in healthy humans or dogs [9,23,82], indicating that inhibition of PRA is not dependent on ANP in this setting. Generally, as has been recently discussed in detail [23], even large changes in salt load, either by infusion or oral salt intake, only evoke rather small increases in plasma ANP levels.…”
Section: Anpmentioning
confidence: 88%
See 2 more Smart Citations
“…Because ANP plasma levels are elevated under significant salt load and ANP can suppress renin release, a functional role of ANP in the salt-dependent regulation of PRA appears plausible. However, modest, acute salt loading by NaCl infusion at rates that did not elevate plasma ANP levels suppressed the plasma renin activity in healthy humans or dogs [9,23,82], indicating that inhibition of PRA is not dependent on ANP in this setting. Generally, as has been recently discussed in detail [23], even large changes in salt load, either by infusion or oral salt intake, only evoke rather small increases in plasma ANP levels.…”
Section: Anpmentioning
confidence: 88%
“…Thus, slow salt loading by an infusion of saline markedly suppressed PRA without any detectable changes in the arterial blood pressure [82] or even a slight decrease in blood pressure in humans [2]. Similarly, PRC was reduced by a saline infusion in dogs without any detectable changes in MABP [9].…”
Section: Regulation Of the Renin System By Salt-dependent Changes In mentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, it was shown that the natriuresis in response to sodium load, which increased blood pressure, was inhibited by the administration of ANG II, suggesting that a decrease in the RAS is a prerequisite for the natriuretic response to sodium load (21, 74). Subsequent elegant studies in humans and laboratory animals further suggest that the suppression of renin release in response to an acute modest sodium load is not only independent of changes in blood pressure, but also independent of cardiac output, GFR, ANP, ␤ 1 -adrenergic receptors, plasma sodium levels, osmolality, renal nerves, and nNOS-derived NO (73,456,593,717). Therefore, the question arises which mechanism(s) mediates natriuresis and suppression of renin in response to an acute modest sodium load.…”
Section: B Salt Intakementioning
confidence: 99%
“…Other candidates that have been considered as possible mediators of salt balance on renin expression are hormones such as atrial natriuretic peptide, which could inhibit renin expression during extracellular volume expansion, or renal nerves, which might stimulate renin expression during salt depletion. However, neither renal innervation, ␤-adrenoreceptors, nor atrial natriuretic peptides appear to be essential for the regulation of renin expression by salt balance (2,16,18,28). Finally, also a mediator function of renal perfusion pressure is conceivable because the perfusion is known to affect renin expression (29) and the metaplastic phenotype switch in preglomerular arteries (13).…”
mentioning
confidence: 99%